Sistem Pendukung Keputusan dalam Memilih Motif Batik Berdasarkan Minat Konsumen - Hidayat, Muhammmad Ridyan Agung; , Muhammad Kusban, S.T.,M.T (2016)
Batik is a traditional fabric that has many motives, batik-making process has some way and each process produces a unique motif. Solo city has many traditional batik motifs and contemporary, it makes consumers confused to choose what batik suit the tastes but in harmony with the usability of batik that later. Therefore it takes a decision support system to facilitate the public to choose the appropriate motif. The method used in compiling this system is AHP (analytical hierarchy process). AHP is a decision making tool which is compiled from a variety of options that can be criteria that has previously been decomposed beforehand. Making the results of this system is emerging batik results in accordance with user input and refers to the weighting of each alternative and the criteria in AHP. Results of the application in ujikan to 10 randomly selected respondents. based on these test results, 71.42% stated that consumers are satisfied with the application that created and can help people choose the desired model of batik.